Aggressive behavior prevention in a dance duet - Olena Gant; Serhii Tkachov; Eduard Valiuh (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study the features of aggression and the main directions of prevention of aggressive forms of behavior, among athletes engaged in sports dancing in the preliminary basic training. Material & Methods: analysis of scientific and methodological literature, "Personal aggressiveness and conflictness". Results: a theoretical analysis of the problem of aggressive behavior in sports dance duets. Level of aggressiveness of athletes of sports dances at the stage of preliminary basic training is determined. Reasons for the formation of aggressive behavior among young athletes are revealed. Areas of preventive and psychocorrectional work with aggressive athletes are singled out. Conclusion: a high level of aggression was detected in 19 (31,67%) of the study participants. Determinants of aggressive behavior in sport ballroom pair appear particularly family upbringing style and pedagogical activity of the trainer. Correction of aggressive behavior of young athletes should have a complex systemic character and take into account the main characterological features of aggressive athletes.